2023
DOI: 10.59440/ceer/172510
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Numerical Analyses of Steel-timber Composite Beams with LVL Slabs

Julia Strzelecka,
Łukasz Polus,
Marcin Chybiński

Abstract: Recently conducted studies have shown that significant benefits are to be gained by joining steel beams and timber slabs. Steel-timber composite beams present a sustainable solution for the construction industry because of their high strength and stiffness, and lower carbon footprint and self-weight than steel-concrete composite beams. The behaviour of steel-timber composite beams is still being investigated to reduce knowledge gaps. This paper presents theoretical and numerical analyses of steel-timber compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Huang et al [ 21 ] analyzed the influence of atmospheric and hydrothermal factors on the behavior of LVL beams with a hybrid glass-flax composite, observing a decrease in bending strength with an increase in beam ductility. Strzelecka et al [ 22 ] conducted theoretical and numerical studies on the use of composite steel-veneer beams consisting of a steel section and an LVL plate. The behavior of layered wooden beams in fire conditions was presented in the work [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [ 21 ] analyzed the influence of atmospheric and hydrothermal factors on the behavior of LVL beams with a hybrid glass-flax composite, observing a decrease in bending strength with an increase in beam ductility. Strzelecka et al [ 22 ] conducted theoretical and numerical studies on the use of composite steel-veneer beams consisting of a steel section and an LVL plate. The behavior of layered wooden beams in fire conditions was presented in the work [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Composite beams can be designed analytically assuming a stiff connection method. This shows the importance of the joining technology used [ 18 ]. Adhesive bonding is particularly important in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term tests of hybrid bending beams have shown that bending stiffness and load-bearing capacity can be significantly increased (3–4 times) compared to pure timber beams. The importance of material joining technology has been confirmed [ 6 ]. In this context, bonding is particularly important.…”
mentioning
confidence: 99%